Complications Related to Insertion and Use of Central Venous Catheters (CVC) - Hodzic, Samir (Med Arch, 2014)
INTRODUCTION: Central Venous Catheters (CVC) are essential in everyday medical practice, especially in treating patients in intensive care units (ICU). The application of these catheters is accompanied with the risk of complications, such as the complications caused during the CVC insertion, infections at the location of the insertion, and complications during the use of the catheter, sepsis and other metastatic infections. PATIENTS AND METHODS: This study is a retrospective-prospective and it was implemented in the period 1(st) January 2011- 31(st) December 2012. It included 108 examinees with CVC placed for more than 7 days. RESULTS: The most common complications occurring in more than 2 attempts of CVC applications are: hearth arrhythmias in both groups in 12 cases, 7 in multi-lumen (12.72%) and 5 in mono-lumen ones (9.43%). Artery puncture occurs in both groups in 7 cases, 5 in multi-lumen (9.09%) and 2 in mono-lumen ones (3.77%). Hematoma occurred in both groups in 4 cases, 3 in multi-lumen CVCs (5.45%) and 1 in mono-lumen ones (1.88%). The most common complication in multi-lumen catheters was heart arrhythmia, in 20 cases (36.37%). The most common complications in mono-lumen CVCs was hearth arrhythmias, in 20 cases as extrasystoles and they were registered in 16 catheter insertions (30.18%). Out of total number of catheters of both groups, out of 108 catheters the complications during insertion occurred in 49 catheters (45.40%). The most common complications in both groups were heart arrhythmias, artery punctures and hematomas at the place of catheter insertion.